2016
DOI: 10.1007/s00383-016-3907-0
|View full text |Cite
|
Sign up to set email alerts
|

Current practice patterns of rectal suction biopsy in the diagnostic work-up of Hirschsprung’s disease: results from an international survey

Abstract: Although RSB is considered to be today's gold standard for the diagnosis of HD, many aspects of its current usage are lacking consensus. Therefore, a prospective multi-center study or larger global audit appears warranted to identify if the present survey reflects common surgical practice and to establish universal standards for RSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…6 Another recent questionnaire distributed to participants and faculty members at the 21st International Meeting of the Pediatric Colorectal Society (78% staff surgeons representing 30 countries) found that 15% of respondents prefer open fullthickness biopsy under general anesthesia for the evaluation of suspected Hirschsprung's disease. 4 Among those surgeons using SRB for the diagnosis, there was a wide variety in the device used as well as the technique of obtaining tissue samples. A median of 10% (range, 0-40%) of biopsies were reported to be insufficient requiring a repeat SRB or open full-thickness biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Another recent questionnaire distributed to participants and faculty members at the 21st International Meeting of the Pediatric Colorectal Society (78% staff surgeons representing 30 countries) found that 15% of respondents prefer open fullthickness biopsy under general anesthesia for the evaluation of suspected Hirschsprung's disease. 4 Among those surgeons using SRB for the diagnosis, there was a wide variety in the device used as well as the technique of obtaining tissue samples. A median of 10% (range, 0-40%) of biopsies were reported to be insufficient requiring a repeat SRB or open full-thickness biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Suction rectal biopsy (SRB) has been considered the gold standard for the diagnosis of Hirschsprung's disease. 4 However, a recent study conducted in the Netherlands questioned the accuracy of SRB, especially regarding its utility in neonates. The authors recommended delaying rectal biopsy until at least 39 days of age due to a false-negative rate of 20.7% in infants younger than this.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, adequate submucosal tissue was absent in about half of the patients in the rectal suction biopsy group . In other studies, about 10–20% of rectal suction biopsies proved to be inadequate either due to small size or insufficient inclusion of submucosa . Therefore, endoscopic sampling using band‐EMR can be a useful alternative to the conventional biopsy techniques.…”
Section: Discussionmentioning
confidence: 79%
“…These findings are compatible with previous studies [17, 18]. Although the diagnostic accuracy of HE staining is relatively lower than that of calretinin and AChE staining, a recent study has revealed that the most frequently used staining methods for rectal biopsies were HE (75.9%) and AChE (73.6%; sensitivity and specificity: 96.8% and 99.4%, respectively), followed by calretinin (33.3%; sensitivity and specificity: 99.1% and 100%, respectively) [7, 10, 19]. Moreover, the use of a variety of complimentary staining tools with HE helps to further increase the diagnostic accuracies by histology, including AChE, calretinin, and S100 [7, 9, 10, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…While immunohistochemistry (IHC) methods have been widely used for the diagnosis of HSCR in developed countries [6], there are very few studies of their use in developing countries where hematoxylin and eosin (HE) staining is the important element of HSCR diagnosis [7]. …”
Section: Introductionmentioning
confidence: 99%